2016
DOI: 10.1111/jphp.12596
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A inhibits TGF-β1-induced activation of human fetal lung fibroblastsin vitro

Abstract: These findings suggest that HSYA inhibits TGF-β1-induced activation of MRC-5 cells associated with TGF-β1/Smad and ERK/MAPK signalling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Previously, we showed that MRC-5 cells treated with HSYA for 72 h could inhibit TGF-β1-induced cell proliferation in a dose-dependent manner (Pan et al, 2016). To determine how early this effect appeared, we monitored the effect of HSYA on TGF-β1-induced cell proliferation after 24, 48, or 72 h. As depicted in Supplementary Figure S1 , the OD measure of proliferation of MRC-5 cells was lower in the TGF-β1+HSYA treated group as compared to the group treated with TGF-β1 alone after 48 or 72 h. This effect was dose dependent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we showed that MRC-5 cells treated with HSYA for 72 h could inhibit TGF-β1-induced cell proliferation in a dose-dependent manner (Pan et al, 2016). To determine how early this effect appeared, we monitored the effect of HSYA on TGF-β1-induced cell proliferation after 24, 48, or 72 h. As depicted in Supplementary Figure S1 , the OD measure of proliferation of MRC-5 cells was lower in the TGF-β1+HSYA treated group as compared to the group treated with TGF-β1 alone after 48 or 72 h. This effect was dose dependent.…”
Section: Resultsmentioning
confidence: 99%
“…HSYA analysis was performed using a high-performance liquid chromatography system (Wang Y. et al, 2014). The purity of the HSYA was previously determined by the area normalization method to be 95.2% (Pan et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, TGF-. TGFSmad Smad extracellular signalregulated kinase (ERK), c-Jun-N-terminal kinase (JNK), p38 MAPK mitogen activated protein (MAP) kinases phosphoinositide 3-kinase/Akt (PI3K/Akt) (Pan et al, 2016). fucoidan 4 cells/mL and incubated with various fucoidan concentrations (1, 5, and 10 µg/mL) for 1 h prior to TGF-β1 stimulation (1 ng/mL).…”
Section: 결과 및 고찰mentioning
confidence: 99%